2004
DOI: 10.1111/j.1708-8240.2004.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cavity Configuration on Microleakage around Class V Restorations Bonded with Seven Self‐Etching Adhesives

Abstract: Comparisons of both gingival and enamel margins within each of the groups showed no significant difference owing to configuration factor (C-factor; p > .5 in all cases, calculated with Kruskal-Wallis nonparametric analysis of variance [ANOVA]) and Dunn's multiple comparison test). All groups showed microleakage at the gingival margins irrespective of C-factor or bonding agent (box-shaped cavities, p = .8862; V-shaped cavities, p = .9623; using the ANOVA). Microleakage was not observed at all enamel margins reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 22 publications
4
47
1
6
Order By: Relevance
“…[1][2][3]9,16,[19][20][21][22] Morphological and histological considerations, and other clinical factors causing inadequate bonding at the material/tooth surface interface, include cavity configuration (C-factor) and dentinal tubule/enamel rod orientation, capillary movement of dentinal tubular fluids, physical characteristics of the restorative material (filler loading, volumetric expansion, modulus of elasticity and polymerization contraction), inadequate margin adaptation of the restorative material during insertion, inappropriate barrier protection (dental rubber dam), tooth location, occlusal stresses/tooth flexure and patient age considerations. [23][24][25][26][27][28][29][30][31] In this study, since hybrid layer morphology was not evaluated microscopically, the specific nature of restoration failure (microleakage) for each adhesive system is unknown, although several factors were strongly suspected: inefficiency of acidic monomers in alteration of the smear layer for classic hybrid layer formation, cavity C-factor, orientation of dentinal tubules/enamel rods to the cementoenamel junction, use of acetone-based solvent primer systems and post-treatment stresses caused by polymerization contraction.…”
mentioning
confidence: 99%
“…[1][2][3]9,16,[19][20][21][22] Morphological and histological considerations, and other clinical factors causing inadequate bonding at the material/tooth surface interface, include cavity configuration (C-factor) and dentinal tubule/enamel rod orientation, capillary movement of dentinal tubular fluids, physical characteristics of the restorative material (filler loading, volumetric expansion, modulus of elasticity and polymerization contraction), inadequate margin adaptation of the restorative material during insertion, inappropriate barrier protection (dental rubber dam), tooth location, occlusal stresses/tooth flexure and patient age considerations. [23][24][25][26][27][28][29][30][31] In this study, since hybrid layer morphology was not evaluated microscopically, the specific nature of restoration failure (microleakage) for each adhesive system is unknown, although several factors were strongly suspected: inefficiency of acidic monomers in alteration of the smear layer for classic hybrid layer formation, cavity C-factor, orientation of dentinal tubules/enamel rods to the cementoenamel junction, use of acetone-based solvent primer systems and post-treatment stresses caused by polymerization contraction.…”
mentioning
confidence: 99%
“…Çal›şmam›zda kullan›lan self-etch adezivler (Optibond Solo Plus SE ve Prompt L-Pop) mine yüzeylerinde yeterli örtücülüğü sağlam›ş ve diğer tek şişe sistemler gibi benzer örtücülük sergilemiştir. Bu sonuçlar diğer çal›şmalar ile paralellik göstermektedir (6,8,13,18).…”
Section: Discussionunclassified
“…Son zamanlarda yap›lan çal›şmalarda, servikal kavitelerin mine kenarlar›nda tek şişe bonding sistemi kullan›ld›ğ›nda, self-etch sistemlere göre daha az mikros›z›nt› gösterdiği bildirilmiştir (7,12). Ancak, baz› araşt›r›c›lar, self-etch sistemleri ile tek şişe bonding sistemleri aras›nda, S›n›f V kavitelerde, mikros›z›nt› değerleri aras›nda bir fark bulamad›klar›n› rapor etmişlerdir (13,14). Atash ve ark (6) ise selfetch sistemlerinin S›n›f V kaviterlerde hem mine hem de gingival kenarlarda çok iyi bir örtücülük sağlad›ğ›n› bildirmişlerdir.…”
Section: Introductionunclassified
“…The study of Santini et al (2004), focused on evaluation of microgaps, showed no significant differences between the use of different types of self-etching agents and the technique of total etching with 36% phosphoric acid. Fabianelli et al (2003) compared marginal leakages between composite materials and hard dental tissues and observed a worse marginal leakage of composite materials in the cervical area copared to occlusion.…”
Section: Discussionmentioning
confidence: 99%